The Effectiveness of Socrative in Learning Reading Comprehension at Ninth Grade of Junior High School Al Hidayah - Layla Azyzatur Roviqoh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study investigates wether there is any significant difference between the students who taught using Socrative and those who are not taught using Socrative in Junior High School Al Hidayah. Fourthy one students from ninth grade of Junior High School Al Hidayah were involved in this study. These students were required to do pre-test, treatment, and post-test using Socrative. The researcher applied quasi experiment research which the pre-test was given firstly to determine them into the control and experimental group. The finding of this study shows that there is difference in students’ reading comprehension between the experimental group and control group. The mean score from both groups in reading comprehension, the experimental group, M=77,05, and the control group, M=69,23. The mean difference between both two groups is 7,82. The experimental group records higher than the control group; this implies that the English teachers can take advantages from using Socrative in learning reading comprehension. Also, the English teachers should use a variety of strategies and methods so that students are not bored during the teaching and learning process. It is expected that this research can be beneficial for future researcher as a reference to conduct in depth study, especially for the same topic as the present study.